The impact of refractive technologies Femto Lasіk and ReLEx SMILE on the development of dry eye syndrome and the quality composition of tears in eyes with myopia and myopic astigmatism - Zavhorodnia, N. H.; Doroshenko, Yu. Yu.; Poplavska, I. O. (Pathologia, 2024)
Aim. To improve the quality of surgical treatment of myopia and myopic astigmatism by refining the indications for the selection of the correction method based on the study of tear crystallography. Materials and methods. The article presents the results of the surgical treatment of 45 patients (90 eyes) with mild and moderate myopia and myopic astigmatism, who underwent vision correction using ReLEx SMILE and Femto Lasіk methods at the Visus Clinic of Modern Ophthalmology (Zaporizhzhia). Among the patients, there were 20 (45 %) men and 25 (55 %) women aged between 19 and 38 years (mean age 27.28 ± 1.08 years). They were divided into two groups. The first group consisted of 25 patients (50 eyes) who underwent vision correction using the ReLEx SMILE method. The second group included 15 patients (30 eyes) who underwent vision correction using the Femto Lasіk method. All patients underwent standard ophthalmological examinations, refractive diagnostics, and tear crystallography. Results. In the postoperative period, the location and number of salt crystals in the central zone slightly changed. In the first group, multiple randomly located quadrangular crystals appeared in 6 eyes (12.0 %) compared to 2 eyes (4.0 %) before surgery. In the second group, these crystals were observed in 4 eyes (13.3 %), indicating minor changes in the salt component of the tear fluid, slightly more pronounced in the second group. Conclusions. The study showed a minor impact of Femto Lasіk and ReLEx SMILE refractive surgeries on the protein-electrolyte state of the tear. Within a month after refractive surgery, the protein-salt composition of the tear, according to crystallography data, fully recovered in 96.0 % of cases where the ReLEx SMILE method was used and in 86.7 % of cases where the Femto Lasіk method was used (statistically significant difference p < 0.05). This allows for a preference for the ReLEx SMILE method when choosing a correction method for refractive anomalies, especially in eyes showing signs of dry eye syndrome.